Recent Advancements and Development in Nano-Enabled Agriculture for Improving Abiotic Stress Tolerance in Plants - Manzoor, Natasha; Ali, Liaqat; Ahmed, Temoor; Noman, Muhammad; Adrees, Muhammad; Shahid, Muhammad Shafiq; Ogunyemi, Solabomi Olaitan; Radwan, Khlode S. A.; Wang, Gang; Zaki, Haitham E. M. (Frontiers in Plant Science, 2022)
Abiotic stresses, such as heavy metals (HMs), drought, salinity and water logging, are the foremost limiting factors that adversely affect the plant growth and crop productivity worldwide. The plants respond to such stresses by activating a series of intricate mechanisms that subsequently alter the morpho-physiological and biochemical processes. Over the past few decades, abiotic stresses in plants have been managed through marker-assisted breeding, conventional breeding, and genetic engineering approaches. With technological advancement, efficient strategies are required to cope with the harmful effects of abiotic environmental constraints to develop sustainable agriculture systems of crop production. Recently, nanotechnology has emerged as an attractive area of study with potential applications in the agricultural science, including mitigating the impacts of climate change, increasing nutrient utilization efficiency and abiotic stress management. Nanoparticles (NPs), as nanofertilizers, have gained significant attention due to their high surface area to volume ratio, eco-friendly nature, low cost, unique physicochemical properties, and improved plant productivity. Several studies have revealed the potential role of NPs in abiotic stress management. This review aims to emphasize the role of NPs in managing abiotic stresses and growth promotion to develop a cost-effective and environment friendly strategy for the future agricultural sustainability.